Pembelajaran Matematika Aktif dan Menyenangkan: Implementasi Media Kartu Domino untuk Meningkatkan Hasil Belajar Siswa - Anggraeni, Fitri; Salahudin, Anas; Rohmah, Siti Khozanatu (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Mathematics learning in Madrasah Ibtidaiyah, particularly on fraction topics, is often perceived as difficult by students, which negatively affects cognitive learning outcomes and active participation in the learning process. This condition indicates the need for an instructional approach that encourages student engagement while facilitating concrete conceptual understanding. This study aims to examine the effectiveness of an active learning approach using domino card media in teaching fractions to fourth-grade students at Madrasah Ibtidaiyah. The study employed a quantitative approach with a quasi-experimental Design involving two groups: an experimental class implementing active learning supported by domino cards and a control class applying conventional instruction without learning media. Data were collected through pretests and posttests to measure students’ cognitive learning outcomes, as well as observation sheets to assess the implementation of the learning process. Data analysis was conducted using the Wilcoxon test and the independent-samples t-test with SPSS version 22. The results show that the active learning approach using domino cards was implemented effectively and significantly increased student engagement during mathematics learning. In addition, students in the experimental class demonstrated substantial improvement in cognitive learning outcomes and achieved higher posttest scores than those in the control class. These findings confirm that integrating active learning with domino card media is efficacious in improving students’ understanding of fractions and contributes positively to the quality of mathematics instruction in Madrasah Ibtidaiyah.